2006
DOI: 10.1071/sr05135
|View full text |Cite
|
Sign up to set email alerts
|

Sampling considerations for surveying copper concentrations in Australian vineyard soils

Abstract: The Australian wine industry has funded a study to determine the concentrations of copper in vineyard soils and to assess whether the continued use of copper-based fungicides is likely to be detrimental to the long-term agricultural sustainability of vineyard soils. Prior to the conduct of regional surveys to determine copper concentrations in vineyard soils, a preliminary study was conducted in 6 vineyards near Mildura (34°S, 142°E) (north-western Vic., Australia) to determine sampling considerations. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…In particular, the total Cu concentrations in the present study are consistent with those found in the soils of vineyards in Italy (mean 130 mg kg -1 , Deluisa et al, 1996), France (mean 99 mg kg -1 , Brun et al, 1998) and NW Iberian Peninsula (mean 163 mg kg -1 , Fernández-Calviño et al, 2009). The levels of concentrations tend to be lower than those found in our study for the Australian vineyards (Wightwick et al, 2006) and for vineyards from the Czech Republic (Komárek et al, 2008), probably due to the lower average annual usage of Cu-based fungicides. On the contrary, Cu concentrations in Brazilian vineyards and in vineyards from Champagne area, France, can reach up to 3200 mg/kg -1 and 1500 mg/kg -1 respectively, because of the exceptionally high volumes of fungicides that are needed in areas with greater humidity and precipitation for diminishing downy mildew attacks (Mirlean et al, 2007).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In particular, the total Cu concentrations in the present study are consistent with those found in the soils of vineyards in Italy (mean 130 mg kg -1 , Deluisa et al, 1996), France (mean 99 mg kg -1 , Brun et al, 1998) and NW Iberian Peninsula (mean 163 mg kg -1 , Fernández-Calviño et al, 2009). The levels of concentrations tend to be lower than those found in our study for the Australian vineyards (Wightwick et al, 2006) and for vineyards from the Czech Republic (Komárek et al, 2008), probably due to the lower average annual usage of Cu-based fungicides. On the contrary, Cu concentrations in Brazilian vineyards and in vineyards from Champagne area, France, can reach up to 3200 mg/kg -1 and 1500 mg/kg -1 respectively, because of the exceptionally high volumes of fungicides that are needed in areas with greater humidity and precipitation for diminishing downy mildew attacks (Mirlean et al, 2007).…”
Section: Discussioncontrasting
confidence: 50%
“…1). We specifically followed the recommendations given by Wightwick et al (2006) who suggested the collection of one composite sample from as many vineyards in a region as possible instead of collecting many samples from fewer vineyards. In each vineyard, soil samples were collected from the surface soil (20 cm depth) from the middle row in the vineyard.…”
Section: Soil Sampling and Preparationmentioning
confidence: 99%
“…(Mirlean et al 2009 ;Komárek et al 2010 ;Pavlovic 2011 ). The highest Cu concentrations occur usually in the surface soil layers (Pietrzak and McPhail 2004 ;Wightwick et al 2006 ;Mirlean et al 2007 ), where they may be as high as in the range 500-1,000 mg/kg. The maximum value of 3,216 mg/kg was reported from a subtropical region in Brazil (Mirlean et al 2007 ).…”
Section: Fertilizers and Pesticides As Sources Of Cu In Agricultural mentioning
confidence: 99%
“…Authors have argued that the "within-vineyard variation" should be taken into consideration in soil sampling (Wightwick et al 2006). Recently, in order to learn the influences of long-term application of Cu-based fungicides on soil microbial communities in vineyard, Mackie et al (2013) have collected soil samples by a 0.25 m by 0.25 m grid, and significant difference was found between the samples.…”
Section: Introductionmentioning
confidence: 98%